Implicaciones De La Practica Del Judo En La Institución Educativa Camilo Torres De La Ciudad Armenia, Quindío- Colombia. (2016)
Between the last months of 2015 and beginnings 2016, it´s been done a investigative research called “Implications of the Judo practice in the armenia´s Cmilo Torres Education facility in Quindio Colombia” .This investigation has the main objetive was to reveal the implicationes of the Judo practice in the mentioned Institucion . to bring thid planififf to a good end, it was token from theview of a qualitative focus, using the reflexive ethnographics as the main tool for the process. Deep interview was the cannel to obtain the information wich was made to some relatives also. And members of the institution stiff, to bring a clearer idea of the implications that this sport bring to comunity. The most relevant results, were the downing.bringing of the selfcounciousness, at the some time the students improved the comunication channels, bringing better socialization procss which improved the affective competitions of the students. In the family sphere become a sense of unity all of this make easy the educational tardets on every aspect